INSTAGRAM DAN MITOS KECANTIKAN PEREMPUAN MUSLIM - Yessy Hermawati; Aquarini Piyatna; Mohamad Adji (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
This study analyzed the discourse about the beauty myth of Muslim women in social media Instagram. This study is an important and interesting because in the Instagram social media, Muslim women have contributed to form the concept of modern female beauty through fashion hijab. The method used in this study is a qualitative analysis using a discourse that refers to a combination of female discourse Sara Mills theory and the theory of Roland Barthes myth. Data used in the form of images, tagline, and text contained in Instagram account some Indonesian Muslim women. Through analysis of the data known that the discourse displayed in Instagram account Muslim women to contribute to the formation of the myth of female beauty. There are three kinds of beauty, which is pretty spiritual, physical gorgeous, and ethics which is a combination of the two. The patriarchal culture still influences the beauty myth in the Instagram account. Women in Instagram account which comes with hijab fashion has the power to add to the beauty. Muslim women's experience in the media commodification.